Exploring Determinant Factors Contributing to Students’ Choices in Selecting English Study Program (A Study at English Study Program of FKIP Tanjungpura University in Pontianak) - Clarry Sada (STKIP Singkawang, 2021)
This study aims at exploring the determinant factors contributing to students’ choice in selecting English Study Program (A Study on English Study Program at FKIP Tanjungpura University in Pontianak). It has been noticed that some of the students have a low qualification of English skill, therefore, it has become a problem for those students to follow the lesson. It has assumed that the students do not have sufficient information on their selection of choosing English Study Program. The problems of this study are: (1) What are the determinant factors influenced the students’ choice in selecting the English study program of FKIP University of Tanjungpura in Pontianak ?. And (2) What are the dominant determinant factors influenced the students’ choice in selecting the English study program of FKIP at the University of Tanjungpura in Pontianak ?. The purposes of the study are: (1) to find out the determinant factors influenced the students’ choice of selecting the English study program, (2) to identify the dominant determinant factors influenced the students’ choice in selecting the English study program, and (3) to identify the deviation attitudes of the students in selecting English study program. The method uses questionnaires which contain some information to be answered by the students. There are 30 respondents as a sample of this research. The findings show that (1) the determinant factors are: a personal choice, the reputation of faculty, the reputation of the study program, teachers and parents, and a location. Meanwhile, the dominant determinant factors are (1) a personal choice (137), the reputation of the study program (119), teachers (111) and parents (107).